Dragons of the deep (Stomiiformes: Stomiidae): Evolutionary relationships and taxonomy of the barbeled dragonfishes (Stomiinae) and viperfishes (Chauliodontinae) - Dearmon, Emily S.; Smith, W. Leo; Davis, Matthew P. (Zootaxa, 2026)
The stomiiforms are a diverse radiation of ray-finned fishes found in pelagic deep-sea environments, with taxa encompassing the barbeled dragonfishes including more than 350 species placed in the family Stomiidae. Barbeled dragonfishes are a diverse lineage of stomiiforms with most taxa and nearly all stomiines having a bioluminescent chin barbel that is hypothesized to be used for conspecific communication and prey attraction. Prior studies on the evolutionary relationships of the stomiids have produced conflicting hypotheses regarding the monophyly of the order’s families and subfamilies and the interrelationships among genera. In this study, we investigate the evolutionary relationships among the stomiids and present a novel hypothesis of evolutionary relationships for the family based on data from ultraconserved elements (UCEs), protein-coding gene fragments, and morphology. Our combined dataset includes 29 of the 35 currently recognized stomiid genera sensu Smith et al. (2024) with taxonomic representatives from all previously recognized stomiid subfamilies and tribes. Our resulting evolutionary hypotheses conflict with the current classification of the family, rendering several currently recognized clades as para- or polyphyletic. These findings necessitate a revised classification that reflects monophyletic groups. Herein, we present a revised classification of the Stomiidae that recognizes the distinct tribal lineages of the barbeled dragonfishes.